EKSPLORASI ETNOMATEMATIKA BUDAYA MASYARAKAT INSANA BARAT - Justin Eduardo Simarmata; Stanislaus Amsikan; Elizio Victor De Araujo (JURNAL EDUSCIENCE, 2022)
This study aims to determine the mathematical concepts contained in woven fabrics, lopo, musical instruments and plant patterns in West Insana Sub-District, Timor Tengah Utara District. The type of research used is descriptive qualitative research. Descriptive qualitative research with ethnographic approach. The location of this research was in West Insana Sub-District, Timor Tengah Utara District, Nusa Tenggara Timur (NTT). The objects of this research are woven fabrics, lopos, musical instruments and cropping patterns from an ethnomathematical point of view in the culture of the West Insana community. In this paper sources of data used are primary data and secondary data. The results obtained are mathematical concepts in the Sotis weaving motif, namely the concept of a square, triangle and rhombus, in Lopo there are concepts of cones, circles and tubes, on musical instruments (gongs and drums) there are concepts of circles and tubes, and on cropping patterns (corn ) there are concepts of quadrangle, circles and straight lines on woven fabrics, lopo, musical instruments and plant patterns there are cultural values, namely discipline and social values.